Preparation technology of short fiber molded carbon / carbon brake disc prepreg
By combining the short fiber molding process and the borate phenol ester nanocomposite, a prepreg for carbon/carbon brake disc was prepared, which solved the problems of poor friction and wearability of the brake disc and low carbon-forming rate in the prior art, and achieved significant Improve performance and become a high-performance green and environmentally friendly friction material.
Patent Information
- Application Number
- CN202311554280.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-11-21
AI Technical Summary
The existing prepregs for brake discs have poor friction and wearability and low carbonization rate, resulting in poor brake disc performance.
The prepreg for carbon/carbon brake discs is prepared by using a short fiber molding process combined with the borate phenol ester nanocomposite material. The phenol borate ester nanocomposite used in this process can significantly improve the carbon formation rate of the phenolic resin and improve the friction and wear properties of carbon fibers through specific chemical reactions.
It significantly improves the friction and wear performance of the brake disc, improves the friction coefficient and recovery performance, making it a high-performance, pollution-free green and environmentally friendly friction material.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brake disc preparation, in particular to a preparation process of a prepreg for a short fiber molded carbon / carbon brake disc. Background Art
[0002] Since carbon / carbon composite materials were used to prepare aircraft brake discs in the 1970s, they have been widely used in the brake systems of various aircraft models due to their low density, excellent thermal properties, and stable friction and wear properties. The basic idea of preparing C / C brake discs is to first preform the carbon fiber reinforced material into a preform, and then fill it with matrix carbon to gradually form a dense C / C composite material. At present, there are three methods for preparing C / C brake disc preforms: carbon cloth lamination, carbon fiber and felt lamination needle punching, and short fiber resin impregnation molding. Studies have shown that the organizational structure and various properties of C / C brake discs are different depending on the method of preparing the preform.
[0003] Chinese patent CN108658613B: A method for preparing automobile brake discs by short fiber molding, using short-cut carbon fiber prepreg molding to prepare carbon-based automobile brake discs, and controlling the ratio of short-cut carbon fiber to phenolic resin, using a melt impregnation process to obtain an automobile brake disc preform with a density of ≥1.80g / cm3. Compared with the traditional CVI process and resin impregnation-carbonization process, the short-cut carbon fiber molding process + melt impregnation process quickly obtains a carbon fiber reinforced resin-based composite material through a high-temperature pressing and curing process, and then converts the organic matter in the matrix into inorganic matter through a carbonization process to obtain a porous carbon-based composite material, and finally uses molten silicon to penetrate into the interior of the C / C composite material under the action of capillary force to generate a SiC ceramic matrix. Not only does it greatly shorten the preparation cycle (Table 1), but this composite material has good toughness and strength, and has the characteristics of short production cycle, better toughness and strength.
[0004] Chinese patent CN202115057U: It involves CF mesh reinforced carbon fiber prepreg, which includes a unidirectional carbon fiber layer, a CF mesh, an upper film and a lower film. The CF mesh reinforced prepreg includes a unidirectional carbon fiber layer, a CF mesh, an upper film and a lower film. The CF mesh is pressed on the unidirectional carbon fiber layer, the upper film is on the CF mesh, and the lower film is below the unidirectional carbon fiber layer. The CF mesh reinforced carbon fiber prepreg is produced by processes such as making film, laying yarn, pressing mesh, trial operation, and normal operation. This utility model changes the current situation of high warp strength and low weft strength of unidirectional prepreg, or even no weft strength, and can increase the transverse strength of prepreg by 20%, and the transverse strength of composite materials by more than 20%.
[0005] Chinese Patent CN202157192U: A flattening device for a carbon fiber prepreg dipping production line, provided with a base frame, a rear diverter comb and a front diverter comb on the base frame, a front guide roller at the front of the front diverter comb, a preheater at the front of the rear diverter comb, a pressurized flattening mechanism between the preheater and the front diverter comb, a heating device between the front diverter comb and the front guide roller, the pressurized flattening mechanism includes at least two rollers arranged in parallel, and a flattening tripod is provided between adjacent rollers. After preheating, a pressurized flattening method is adopted to exert the effect of preheating, and a method of reducing the pressurized area and increasing the pressurized pressure is adopted in the pressurization method to improve the flattening effect, and a combination of pressurized flattening and heated flattening is adopted to achieve a better flattening effect, and the smoothness of the fibers after heated flattening is conducive to the composite of fibers and resins in the next composite process.
[0006] The prepregs for brake discs prepared by the above patents and prior art have disadvantages such as poor friction and wear resistance and low carbonization rate. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a preparation process of a short fiber molded carbon / carbon brake disc prepreg, and the operation steps are as follows:
[0008] A1: Weigh 50-70 parts of thiolated carbon fibers by weight, and place them in a dipping device for dipping at 70-90°C for 50-100 minutes;
[0009] The dipping device is equipped with 200-300 parts of boric acid phenol ester nanocomposite material, 10-16 parts of methacrylate 4-boric acid phenol ester, 0.03-0.6 parts of (ferrocenyl) hexanethiol, 0.01-0.1 parts of nickel acrylate, and 2-5 parts of triethylamine, and stirred evenly at room temperature for standby use;
[0010] A2: After impregnation, the prepreg is cut, broken up, and finally sent to hot pressing to obtain short fiber molded carbon / carbon brake disc prepreg.
[0011] The hot pressing temperature is 120-160°C.
[0012] The hot pressing pressure is 4-8Mpa.
[0013] The preparation method of the boric acid phenol ester nanocomposite material is as follows:
[0014] 20-40 parts of boric acid phenol ester, 1-5 parts of vegetable oil, 3-7 parts of nano silicon dioxide and 100-140 parts of DMF are mixed evenly, ultrasonically dispersed for 20-40 minutes, and heated for reaction to obtain a boric acid phenol ester nanocomposite material.
[0015] The reaction temperature is 90-110°C and the reaction time is 3-6h.
[0016] The preparation method of the boric acid phenol ester is:
[0017] In a reaction kettle, add 50-60 parts of phenol, 10-20 parts of boric acid, 100-200 parts of toluene, and 1-5 parts of oxalic acid, stir, mix evenly, and heat to react to obtain boric acid phenol ester.
[0018] The reaction temperature is 90-110°C and the reaction time is 5-8h.
[0019] The preparation method of the thiolated carbon fiber is as follows:
[0020] Place the carbon fiber in the reaction chamber of the plasma surface treatment instrument, pass the steam formed by heating 2-mercaptoethanol into the plasma surface treatment instrument, set the power to 400 and the treatment time to 300. ~ 60min, discharge power is 90 ~ 100W; obtain thiolated carbon fiber.
[0021] The air flow of the 2-mercaptoethanol is 15-30 mL / min.
[0022] Reaction mechanism:
[0023] The thiol groups on the surface of the thiol-modified carbon fibers and the thiol groups of (ferrocenyl) hexanethiol undergo thiol-olefin addition reactions with nickel acrylate and 4-phenyl borate methacrylate, respectively, and the obtained nickel / iron-doped carbon fibers have a stronger bonding effect with the impregnation solution.
[0024] Technical effects:
[0025] The preparation process of a short fiber molded carbon / carbon brake disc prepreg of the present invention has the following significant effects compared with the prior art:
[0026] 1. The boric acid phenol ester nanocomposite material prepared by the present invention can significantly improve the carbonization rate of phenolic resin;
[0027] 2. The short fiber molded carbon / carbon brake disc prepreg prepared by the present invention has significantly improved friction and wear properties, a small friction coefficient and good recovery performance, and can be used as a high-performance, pollution-free, green and environmentally friendly friction material; wherein nickel acrylate and 4-boric acid phenol methacrylate react with the thiol group on the surface of the carbon fiber to change the polarity or wettability of the carbon fiber surface; the impregnation liquid penetrates into the microstructure of the carbon fiber and interacts with the functional groups on the surface of the carbon fiber to form a stronger adhesion; this combination can increase the roughness of the carbon fiber surface and increase the friction coefficient between the carbon fiber and other materials, thereby improving the friction and wear performance of the brake disc, and the nickel / iron-doped carbon fiber may have better mechanical properties and thermal stability, which can also improve the performance of the brake disc. DETAILED DESCRIPTION
[0028] The invention will be further described below by means of specific embodiments:
[0029] 1. Carbonization rate determination method: put the prepreg into a ceramic crucible and use graphite powder to fill it to isolate oxygen oxidation; the carbonization equipment is a box-type resistance heating furnace, the carbonization temperature is 700℃, the insulation time is 2h, and the mass is weighed after natural cooling to room temperature:
[0030] Carbonization rate = mass after carbonization / mass before carbonization X 100%
[0031] 2. Conduct friction and wear tests on a MM1000-II friction and wear testing machine.
[0032] Example 1
[0033] A preparation process of a short fiber molded carbon / carbon brake disc prepreg, the operation steps of which are as follows:
[0034] A1: Weigh 50g of thiolated carbon fiber and put it into a dipping device for dipping at 70℃ for 50 minutes;
[0035] The dipping device is equipped with 200g of boric acid phenol ester nanocomposite material, 10g of methacrylate 4-boric acid phenol ester, 0.03g of (ferrocenyl) hexanethiol, 0.01g of nickel acrylate, and 2g of triethylamine, and stirred evenly at room temperature for later use;
[0036] A2: After impregnation, the prepreg is cut, broken up, and finally sent to hot pressing to obtain short fiber molded carbon / carbon brake disc prepreg.
[0037] The hot pressing temperature is 120°C.
[0038] The hot pressing pressure is 4Mpa.
[0039] The preparation method of the boric acid phenol ester nanocomposite material is as follows:
[0040] 20 g of boric acid phenol ester, 1 g of vegetable oil, 3 g of nano-silicon dioxide, and 100 g of DMF were mixed evenly, ultrasonically dispersed for 20 minutes, and heated for reaction to obtain a boric acid phenol ester nanocomposite material.
[0041] The reaction temperature is 90°C and the reaction time is 3 hours.
[0042] The preparation method of the boric acid phenol ester is:
[0043] In a reaction kettle, add 50 g of phenol, 10 g of boric acid, 100 g of toluene, and 1 g of oxalic acid, stir, mix evenly, and heat to react to obtain boric acid phenol ester.
[0044] The reaction temperature is 90°C and the reaction time is 5 hours.
[0045] The preparation method of the thiolated carbon fiber is as follows:
[0046] The carbon fiber was placed in a reaction chamber of a plasma surface treatment instrument, and the steam formed by heating 2-mercaptoethanol was introduced into the plasma surface treatment instrument. The power was set to a treatment time of 30 min and a discharge power of 90 W; and thiolated carbon fiber was obtained.
[0047] The air flow of the 2-mercaptoethanol is 15 mL / min.
[0048] Example 2
[0049] A preparation process of a short fiber molded carbon / carbon brake disc prepreg, the operation steps of which are as follows:
[0050] A1: Weigh 55g of thiolated carbon fiber and put it into a dipping device for dipping at 75℃ for 60 minutes;
[0051] The dipping device is equipped with 240g of boric acid phenol ester nanocomposite material, 12g of methacrylate 4-boric acid phenol ester, 0.2g of (ferrocenyl) hexanethiol, 0.05g of nickel acrylate, and 3g of triethylamine, and stirred evenly at room temperature for later use;
[0052] A2: After impregnation, the prepreg is cut, broken up, and finally sent to hot pressing to obtain short fiber molded carbon / carbon brake disc prepreg.
[0053] The hot pressing temperature is 130°C.
[0054] The hot pressing pressure is 5Mpa.
[0055] The preparation method of the boric acid phenol ester nanocomposite material is as follows:
[0056] 25 g of boric acid phenol ester, 2 g of vegetable oil, 4 g of nano-silicon dioxide, and 110 g of DMF were mixed evenly, ultrasonically dispersed for 25 minutes, and heated for reaction to obtain a boric acid phenol ester nanocomposite material.
[0057] The reaction temperature is 95°C and the reaction time is 4 hours.
[0058] The preparation method of the boric acid phenol ester is:
[0059] In a reaction kettle, add 54 g of phenol, 13 g of boric acid, 145 g of toluene, and 2 g of oxalic acid, stir, mix evenly, and heat to react to obtain boric acid phenol ester.
[0060] The reaction temperature is 95°C and the reaction time is 5-8h.
[0061] The preparation method of the thiolated carbon fiber is as follows:
[0062] The carbon fiber was placed in a reaction chamber of a plasma surface treatment instrument, and the steam formed by heating 2-mercaptoethanol was introduced into the plasma surface treatment instrument. The power was set to a treatment time of 40 min and a discharge power of 95 W to obtain thiolated carbon fiber.
[0063] The air flow of the 2-mercaptoethanol is 20 mL / min.
[0064] Example 3
[0065] A preparation process of a short fiber molded carbon / carbon brake disc prepreg, the operation steps of which are as follows:
[0066] A1: Weigh 65g of thiolated carbon fiber and put it into a dipping device for dipping at 85℃ for 90 minutes;
[0067] The dipping device is equipped with 280g of boric acid phenol ester nanocomposite material, 14g of methacrylate 4-boric acid phenol ester, 0.4g of (ferrocenyl) hexanethiol, 0.08g of nickel acrylate, and 4g of triethylamine, and stirred evenly at room temperature for later use;
[0068] A2: After impregnation, the prepreg is cut, broken up, and finally sent to hot pressing to obtain short fiber molded carbon / carbon brake disc prepreg.
[0069] The hot pressing temperature is 150°C.
[0070] The hot pressing pressure is 7Mpa.
[0071] The preparation method of the boric acid phenol ester nanocomposite material is as follows:
[0072] 35 g of boric acid phenol ester, 4 g of vegetable oil, 6 g of nano-silicon dioxide, and 130 g of DMF were mixed evenly, ultrasonically dispersed for 35 minutes, and heated for reaction to obtain a boric acid phenol ester nanocomposite material.
[0073] The reaction temperature is 105°C and the reaction time is 5 hours.
[0074] The preparation method of the boric acid phenol ester is:
[0075] In a reaction kettle, add 58 g of phenol, 17 g of boric acid, 180 g of toluene, and 4 g of oxalic acid, stir, mix evenly, and heat to react to obtain boric acid phenol ester.
[0076] The reaction temperature is 105°C and the reaction time is 7 hours.
[0077] The preparation method of the thiolated carbon fiber is as follows:
[0078] The carbon fiber was placed in a reaction chamber of a plasma surface treatment instrument, and steam formed by heating 2-mercaptoethanol was introduced into the plasma surface treatment instrument. The power was set to a treatment time of 50 min and a discharge power of 95 W to obtain thiolated carbon fiber.
[0079] The air flow of the 2-mercaptoethanol is 25 mL / min.
[0080] Example 4
[0081] A preparation process of a short fiber molded carbon / carbon brake disc prepreg, the operation steps of which are as follows:
[0082] A1: Weigh 70g of thiolated carbon fiber and put it into a dipping device for dipping at 90℃ for 100 minutes;
[0083] The dipping device is equipped with 300g boric acid phenol ester nanocomposite material, 16g methacrylate 4-boric acid phenol ester, 0.6g (ferrocenyl) hexanethiol, 0.1g acrylate nickel, and 5g triethylamine, and stirred evenly at room temperature for standby use;
[0084] A2: After impregnation, the prepreg is cut, broken up, and finally sent to hot pressing to obtain short fiber molded carbon / carbon brake disc prepreg.
[0085] The hot pressing temperature is 160°C.
[0086] The hot pressing pressure is 8Mpa.
[0087] The preparation method of the boric acid phenol ester nanocomposite material is as follows:
[0088] 40 g of boric acid phenol ester, 5 g of vegetable oil, 7 g of nano-silicon dioxide, and 140 g of DMF were mixed evenly, ultrasonically dispersed for 40 minutes, and heated for reaction to obtain a boric acid phenol ester nanocomposite material.
[0089] The reaction temperature is 110°C and the reaction time is 6 hours.
[0090] The preparation method of the boric acid phenol ester is:
[0091] In a reaction kettle, add 60 g of phenol, 20 g of boric acid, 200 g of toluene, and 5 g of oxalic acid, stir, mix evenly, and heat to react to obtain boric acid phenol ester.
[0092] The reaction temperature is 110°C and the reaction time is 8 hours.
[0093] The preparation method of the thiolated carbon fiber is as follows:
[0094] The carbon fiber was placed in a reaction chamber of a plasma surface treatment instrument, and the steam formed by heating 2-mercaptoethanol was introduced into the plasma surface treatment instrument. The power was set to a treatment time of 60 minutes and a discharge power of 100 W; and the thiolated carbon fiber was obtained.
[0095] The air flow of the 2-mercaptoethanol is 30 mL / min.
[0096] Comparative Example 1
[0097] The other steps were the same as in Example 1 except that 4-boric acid phenol methacrylate was not added.
[0098] Comparative Example 2
[0099] The other steps were the same as in Example 1 except that (ferrocenyl)hexanethiol was not added.
[0100] Comparative Example 3
[0101] Nickel acrylate was not added, and the other steps were the same as in Example 1.
[0102] Carbonization rate / % Friction coefficient Example 1 83 0.21 Example 2 85 0.19 Example 3 86 0.16 Example 4 87 0.14 Comparative Example 1 52 0.38 Comparative Example 2 63 0.33 Comparative Example 3 66 0.31
[0103] Through the data analysis of the above embodiments and comparative examples, the boric acid phenol ester nanocomposite material prepared by the present invention can significantly improve the carbonization rate of phenolic resin; the short fiber molded carbon / carbon brake disc prepreg prepared by the present invention has a small friction coefficient, significantly improved friction and wear properties, and improved the performance of the brake disc.
Claims
1. A process for preparing a short fiber molded carbon / carbon brake disc prepreg, the operating steps of which are: A1: Weigh 50-70 parts of thiolated carbon fibers by weight, and place them in a dipping device for dipping at 70-90°C for 50-100 minutes; The dipping device is equipped with 200-300 parts of boric acid phenol ester nanocomposite material, 10-16 parts of methacrylate 4-boric acid phenol ester, 0.03-0.6 parts of (ferrocenyl) hexanethiol, 0.01-0.1 parts of nickel acrylate, and 2-5 parts of triethylamine, and stirred evenly at room temperature for standby use; A2: After impregnation, it is cut and scattered, and finally sent to hot pressing to obtain short fiber molded carbon / carbon brake disc prepreg; The preparation method of the boric acid phenol ester nanocomposite material is as follows: 20-40 parts of boric acid phenol ester, 1-5 parts of vegetable oil, 3-7 parts of nano silicon dioxide and 100-140 parts of DMF are mixed evenly, ultrasonically dispersed for 20-40 minutes, and heated for reaction to obtain a boric acid phenol ester nanocomposite material.
2. The process for preparing the short fiber molded carbon / carbon brake disc prepreg according to claim 1, characterized in that: The hot pressing temperature is 120-160°C.
3. The process for preparing the short fiber molded carbon / carbon brake disc prepreg according to claim 1, characterized in that: The hot pressing pressure is 4-8MPa.
4. The process for preparing the short fiber molded carbon / carbon brake disc prepreg according to claim 1, characterized in that: The reaction temperature is 90-110°C and the reaction time is 3-6h.
5. The process for preparing the short fiber molded carbon / carbon brake disc prepreg according to claim 1, characterized in that: The preparation method of the boric acid phenol ester is: In a reaction kettle, add 50-60 parts of phenol, 10-20 parts of boric acid, 100-200 parts of toluene, and 1-5 parts of oxalic acid, stir, mix evenly, and heat to react to obtain boric acid phenol ester.
6. The process for preparing the short fiber molded carbon / carbon brake disc prepreg according to claim 5, characterized in that: The reaction temperature for preparing the boric acid phenol ester is 90-110° C. and the reaction time is 5-8 hours.
7. The process for preparing the short fiber molded carbon / carbon brake disc prepreg according to claim 1, characterized in that: The preparation method of the thiolated carbon fiber is as follows: The carbon fiber is placed in a reaction chamber of a plasma surface treatment instrument, and the steam formed by heating 2-mercaptoethanol is introduced into the plasma surface treatment instrument. The power is set to a treatment time of 30 to 60 minutes and a discharge power of 90 to 100 W; and the thiolated carbon fiber is obtained.
8. The process for preparing the short fiber molded carbon / carbon brake disc prepreg according to claim 7, characterized in that: The air flow of the 2-mercaptoethanol is 15-30 mL / min.
Citation Information
Patent Citations
A method for preparing automotive brake discs by short fiber molding
CN108658613B
CF (carbon fiber) net strengthened carbon fiber prepreg
CN202115057U
Carbon fiber preimpregnation material gum dipping production line flattening device
CN202157192U
Carbon fiber base, prepreg, and carbon-fiber-reinforced composite material
CN103987764A
Method for preparing surface-thiolated carbon fiber based on low-temperature plasma technology
CN108311112A